2016
DOI: 10.1038/ncomms10552
|View full text |Cite
|
Sign up to set email alerts
|

MeCP2 SUMOylation rescues Mecp2-mutant-induced behavioural deficits in a mouse model of Rett syndrome

Abstract: The methyl-CpG-binding protein 2 (MeCP2) gene, MECP2, is an X-linked gene encoding the MeCP2 protein, and mutations of MECP2 cause Rett syndrome (RTT). However, the molecular mechanism of MECP2-mutation-caused RTT is less known. Here we find that MeCP2 could be SUMO-modified by the E3 ligase PIAS1 at Lys-412. MeCP2 phosphorylation (at Ser-421 and Thr-308) facilitates MeCP2 SUMOylation, and MeCP2 SUMOylation is induced by NMDA, IGF-1 and CRF in the rat brain. MeCP2 SUMOylation releases CREB from the repressor c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
67
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(77 citation statements)
references
References 65 publications
8
67
1
Order By: Relevance
“…In a recent study, we have found that IGF-1 and CRF both enhance the SUMOylation of MeCP2 that results in alleviation of Rett syndrome in Mecp2 conditional knockout mice. 57 The present result implicates that IGF-1 and CRF may also alleviate the pathology of AD through enhanced SUMOylation of HDAC1. But dexamethasone, a synthetic glucocorticoid that binds to the glucocorticoid receptor, did not affect HDAC1 SUMOylation.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…In a recent study, we have found that IGF-1 and CRF both enhance the SUMOylation of MeCP2 that results in alleviation of Rett syndrome in Mecp2 conditional knockout mice. 57 The present result implicates that IGF-1 and CRF may also alleviate the pathology of AD through enhanced SUMOylation of HDAC1. But dexamethasone, a synthetic glucocorticoid that binds to the glucocorticoid receptor, did not affect HDAC1 SUMOylation.…”
Section: Discussionsupporting
confidence: 54%
“…25 For construction of the Myc-tagged sumo1 plasmid, the procedure used was the same as that described elsewhere. 57 For construction of the Flag-Mcl-1 plasmid, the procedure used was the same as that described previously. 13 For construction of the Flag-tagged Hdac1 - sumo1 fusion plasmid, the previously cloned Flag-tagged Hdac1 plasmid and Myc-tagged sumo1 plasmid were used as templates and the Hdac1 sequence was amplified with primers 5′-ATCGGGATCCATGGCGCAGACTCAGGGCA-3′ (forward) and 5′-ATCGGATATCGGCCATCTTGACCTCTTCT-3′ (reverse).…”
Section: Methodsmentioning
confidence: 99%
“…Although previous studies failed to demonstrate the genotype‐phenotype correlation regarding stereotypies [Carter et al, ; Temudo, ; Temudo et al, ], p.T158M, p.R168X, p.R270X, p.R106W, and p.R294X mutations were found to be associated with more types of stereotypies in this study. Some pathogenic mutations of MECP2 such as T158M may be associated with more severe phenotype as shown in previous studies [Tai et al, ]. In contrast, individuals with p.R106W, p.R168X, p.R306C, p.R255X, and C806del.G in this study were associated with more severe clinical severities and more advanced stages.…”
Section: Discussionmentioning
confidence: 67%
“…The vast majority of humans with RTT are females with a heterozygous loss of function mutation who are therefore mosaic for the gene (Van den Veyver and Zoghbi, 2000). Mounting evidence from mice that carry mutations abolishing expression of MECP2 strongly suggests that it is an important regulator of plasticity in development and adulthood (Deng et al, 2010;McGraw et al, 2011;Noutel et al, 2011;Na et al, 2013;Deng et al, 2014;He et al, 2014;Krishnan et al, 2015;Tai et al, 2016;Krishnan et al, 2017;Gulmez Karaca et al, 2018). Nevertheless, little is known about how these mutations affect in vivo sensory responses and neurophysiological changes during behavioral learning and plasticity (Durand et al, 2012;Banerjee et al, 2016).…”
Section: Introductionmentioning
confidence: 99%